Trends in HIV/AIDS Infection and Sexual Behaviour Change among Teacher Trainees: A Study of a Teacher-Training College in Western Kenya - H. J. , Mettoh; M. K, Kitainge; J. K , Too (African Journal of Education,Science and Technology (AJEST), 2015)
The available information indicates that so far there is no conclusive cure for HIV/AIDS. The approach taken by various stakeholders to reduce HIV infection do not seem to impact on behaviour change especially among young people (Kenya Aids Indicator Survey, 2007). This study sought to find out whether young people are responding appropriately to sexual behaviour change messages. The study was informed by Rosenstock‟s Modified Health Belief Model (1974). A total of 216 student-teachers were purposively selected. Both survey and causal comparative research designs were adopted. Questionnaires and Focus Group Discussions were used to generate data which was analyzed using descriptive statistics. The study revealed that all the respondents are aware of the most common mode of transmission of HIV infection as sexual intercourse. There was a significant relationship between: year of study and current involvement in sexual relationship; Voluntary Counselling and Testing visits and consideration in choosing sexual partners.